2011
DOI: 10.4236/ojas.2011.13012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacement of soya bean meal by bambara nut sievate on the carcass and organ parameters of finisher broiler chicks

Abstract: Eighty 4-weeks old broiler chicks (Anak 2000 strain) were used in a 28 days feeding trial to determine the effects of replacement of soya bean meal (SBM) by bambara nut sievate (BNS) on the carcass and organ characteristics of fin- isher broiler chicks. BNS replaced soya bean meal by weight for weight at levels 0%, 5%, 10% and 15% for treatments 1,2, 3 and 4; respectively which were replicated four times in a completely randomized design. Feed and potable water were supplied ad libitum to the birds. Also, ap- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…[21] have reported increase in nitrogen-free extract of bambaranut as a result of soaking in water. The values of NFE reported in this work are slightly lower than values (60.89) reported by [22] on roasted bambaranut; the variation can be attributed to cultivars of bambaranut. The different processing methods reduced the calcium content of differently processed bambaranut as reported by [17].…”
Section: Chemical Composition (%) Of the Differently Processed Bambar...contrasting
confidence: 85%
See 1 more Smart Citation
“…[21] have reported increase in nitrogen-free extract of bambaranut as a result of soaking in water. The values of NFE reported in this work are slightly lower than values (60.89) reported by [22] on roasted bambaranut; the variation can be attributed to cultivars of bambaranut. The different processing methods reduced the calcium content of differently processed bambaranut as reported by [17].…”
Section: Chemical Composition (%) Of the Differently Processed Bambar...contrasting
confidence: 85%
“…Slight decrease in ash content in cooked (2.50%) and roasted bambaranut (2.55%) were attributed to leaching and volatization while the slight increase in salt-treated bambaranut is attributed to increase in Na+ and Clions while the ash content of sprouted bambaranut remain fairly constant. Several authors have reported an increase in the ash content of bambaranut [21,22].…”
Section: Chemical Composition (%) Of the Differently Processed Bambar...mentioning
confidence: 99%
“…Livestock production in Nigeria is faced with a lot of problems, one of which is high feed cost. According to Ekenyem [1], feed cost represents about 70-80% of the total cost of production. The increase in the prices of conventional feedstuffs like soya meal, fishmeal and maize which are highly used in the production of animal feed, flour milling, oil industries as well as human consumption is as a result of the competition between humans and animals for grains and upward increase in human population.…”
Section: Introductionmentioning
confidence: 99%